Study the influence of a new ball burnishing technique on the surface roughness of AISI 1018 low carbon steel - Ibrahim, Abd Alkader; Khalil, Tamer; Tawfeek, Tarik (International Journal of Engineering and Technology, 2015)
Hard roller burnishing with a ball tool is a surface-finishing where a free-rotating tool rolls over the machined surface under high pressures and flattens the surface roughness peaks by cold work. In the present work, a new burnishing technique has been applied which enables both single and double ball burnishing process in site after turning without releasing the specimen. Sets of experiments are conducted to investigate the influence of burnishing force, feed, speed and number of tool passes on surface roughness of AISI 1018 Low Carbon Steel specimens. Burnishing results showed significant effectiveness of the new burnishing technique in the process. The results revealed that minimum surface roughness are obtained by applying the double ball burnishing process on AISI 1018 Low Carbon Steel specimens. Improvement in surface finish can be achieved in both single and double ball burnishing by increasing the number of burnishing tool passes. The results are presented in this paper.